2021
DOI: 10.1016/j.jclinepi.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Regression discontinuity analysis demonstrated varied effect of Treat-All on CD4 testing among Southern African countries

Abstract: Regression discontinuity analysis demonstrated varied effect of Treat-All on CD4 testing among Southern African countries,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The recommendation did not prevent people with advanced HIV disease from initiating ART (6,7). However, one study found that the "Treat all" guidelines may have reduced pre-ART CD4 monitoring, weakening advanced HIV disease management (8). One reason for our findings is that several countries began their cervical cancer prevention programmes around 2008, with government support, followed by a rapid scale-up.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The recommendation did not prevent people with advanced HIV disease from initiating ART (6,7). However, one study found that the "Treat all" guidelines may have reduced pre-ART CD4 monitoring, weakening advanced HIV disease management (8). One reason for our findings is that several countries began their cervical cancer prevention programmes around 2008, with government support, followed by a rapid scale-up.…”
Section: Discussionmentioning
confidence: 77%
“…Our result supports the evidence that shows that the recommendations often have heterogeneous impacts on objectives. The guidelines sometimes have unintended consequences (6,7,8,16,17,18). In the United States of America (USA), state insurance mandates to cover costs for Pap smear tests, increased Pap testing rates by 1.3 percentage points among women aged 19_64.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations